Enhancing the moral courage of nurses: A modified Delphi study - Huang, Mingtao (Nursing ethics, 2024)
BackgroundThe urgency of ensuring adequate moral courage in clinical nursing practice is evident. However, currently, there are few formal intervention plans targeted at enhancing the moral courage of nurses.AimTo develop a training program for improving the moral courage of nurses using the modified Delphi method.Research designA modified Delphi study.Participants and research contextFrom November to December 2022, a literature review and expert group discussion were conducted to develop a preliminary training plan framework. From January to March 2023, a two-round Delphi survey was performed, and a consensus was reached regarding the plan through online questionnaires. Descriptive statistics were used to analyze the data.Ethical considerationsThis study was approved by the institutional ethics committee (No. 138, 30 August 2021). All participants provided written informed consent.ResultsConsensus was reached on eight themes and 33 items to strengthen the moral courage training program for nurses.ConclusionsGuided by a unified goal of moral education, a multi-level and acceptable intervention plan was designed to enhance the moral courage of nurses.